Policy regimes and the political economy of poverty reduction in Malaysia - Teik, Khoo Boo; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2012)
Malaysia's 40-year strategy of'poverty eradication' has met with a great deal of success, yet has caused controversy for its links to ethnically-oriented social restructuring. This book is a critical evaluation of changing policy regimes affecting Malaysia's development, record of industrialization, and efficacy in adapting social policies.
Keywords: Political economy; Macroeconomics; International economics; Economic policy; Development economics; Asia -- Economic conditions